A controlled open clinical trial of the positive effect of a physical intervention on quality of life in schizophrenia - Cristiano, Viviane Batista; Szortyka, Michele Fonseca; Belmonte-de-Abreu, Paulo (Frontiers in Psychiatry, 2023)
Justification: Schizophrenia is a severe mental disorder associated with important physical (obesity, low motor functional capacity) and metabolic (diabetes, cardiovascular diseases) changes that contribute to a more sedentary lifestyle and a low quality of life. Objective: the study aimed to measure the effect of two different protocols of physical exercise (aerobic intervention (AI) versus functional intervention (FI)) on lifestyle in schizophrenia compared to healthy sedentary subjects. Methodology: Controlled clinical trial with patients diagnosed with schizophrenia from two different locations (Hospital de Clinicas de Porto Alegre - HCPA and Centro de Atenção Psicosocial - CAPES in the city of Camaquã) and submitted to two different exercise protocols (IA:5-minute warm-up of comfortable intensity; 45-minute aerobic exercise of increasing intensity using any of the 3 modalities: a stationary bicycle, a treadmill, or an elliptical trainer; 10-minute global stretching of large muscle groups; and FI: 5-minute warm-up with stationary walk; 15-minute muscle and joint mobility exercises; 25-minute global muscle resistance exercises; 15-minute breathing body awareness work) twice a week for 12 weeks and compared to physically inactive healthy controls. The clinical symptoms were evaluated (BPRS), life quality (SF-36), and physical activity levels (SIMPAQ). The significance level was p ≤ 0.05. Results: 38 individuals, of which 24 from each group performed the AI, and 14 from each group practiced the FI. This division of interventions was not randomized but for convenience. The cases showed significant improvements in quality of life and lifestyle, but these differences were greater in the healthy controls. Both interventions were very beneficial, with the functional intervention tending to have superiority in the cases and the aerobic intervention in the controls. Conclusions: Supervised physical activity improved life quality and the levels of a sedentary lifestyle in adults with schizophrenia.